Savings mobilisation in developing countries - Uwe Corsepius (Intereconomics, 1988)
Stagnating development aid and continued reluctance on the part of western commercial banks to grant new loans to problem debtor countries have led many developing countries to pay greater attention to the mobilisation of their own resources. This article outlines a strategy for increasing the extent to which domestic savings are made available for development financing.
Keywords: 330; Development Strategy